An Overview of the Relationship Between Menopausal Status and Low Back Pain Complaints at RSUD Cempaka Putih and Its Review Towards Islamic Perspective - Ghani Kamalya; Edi Prasetyo; Karimulloh Karimulloh (PROMOTOR, 2026)
Menopause is a natural physiological phase in women characterized by a decline in estrogen levels, which may affect the musculoskeletal system and increase susceptibility to low back pain (LBP). Low back pain is a common complaint among menopausal women and can interfere with daily activities and quality of life. Nevertheless, evidence regarding the relationship between menopausal status or age at menopause and the intensity of low back pain remains inconsistent, indicating the need for further investigation. This study employed an observational analytic design with a cross-sectional approach. Data were collected from menopausal patients with low back pain at RSUD Cempaka Putih. Pain intensity was assessed using the Numeric Rating Scale (NRS). Data were analyzed using univariate and bivariate statistical analyses. The majority of respondents were menopausal women aged 45–55 years. Most patients experienced moderate pain intensity based on the NRS. Bivariate analysis showed no statistically significant relationship between menopausal status and NRS pain level. There was no significant relationship between menopause and the intensity of low back pain as measured by the Numeric Rating Scale. This finding suggests that low back pain in menopausal women is multifactorial and may be influenced by factors other than menopausal status alone. From an Islamic perspective, maintaining health through appropriate medical treatment and effort (ikhtiar) is part of preserving life (hifz an-nafs).